Similarity and Positivity of Personality Profiles Consistently Predict Relationship Satisfaction in Dyads - Brandstätter, Hermann; Brandstätter, Veronika; Pelka, Rainer B. (Frontiers in Psychology, 2018)
The effect of similarities in the personality traits of romantic partners on their relationship satisfaction (RS) has often been studied, albeit with mixed results. Beyond the main effects of personality traits, incremental validity was often completely missing, or at least very low. In contrast, our five studies, three cross-sectional – including a study on leader-follower dyads to secure generalizability – and two longitudinal, show that, in predicting RS, the beta-coefficients of distance (where distance is defined as the average across items of absolute differences between the two partners’ self-ratings) or positivity (where positivity is defined as the frequency of extremely positive self-ratings) increase when either the positivity of the profiles or the distance between the profiles is added as second predictor. Thus, positivity and distance seem to function as reciprocal suppressor variables that allow controlling for irrelevant components of the predictors. Consequently, when combined with positivity, distance proved to be a consistently better predictor of RS than has been reported in most previous studies. Combining profile distance with profile positivity appears to be promising well beyond research on RS, in that an individual profile of traits can be matched with a profile of a specific environment’s offers and demands when person-environment fit is the focus of interest.